1997
DOI: 10.1177/009539979702800403
|View full text |Cite
|
Sign up to set email alerts
|

Budgetary Reform Through Organizational Learning

Abstract: The legacy of budgetary reform has been dismal. Promising options, rooted in economic values, seem to fall short when confronted with political realities. Nevertheless, the search continues. The authors argue that successful budgetary reform requires attention to the organizational context, in particular human behavioral dynamics. The objectives and execution of budgetary reform must "match" the dynamic objectives and needs of the organization. Moreover, the authors argue that successful implementation require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…These findings about GRB are, again, consistent with the experiences of earlier budget reforms. For instance, Forrester and Adams (1997, p. 473) found that “the chance for successful budget reform increases if executive budget participants and program managers support the goals and objectives of the budget initiative and the legislature participates in the planning process.” They also found that there also must be buy‐in from budget office staff and agency leadership. In many efforts to reform the budget, agencies go through the motions rather than attempting to sincerely implement the reform.…”
Section: Enabling Factors For Grb Successmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings about GRB are, again, consistent with the experiences of earlier budget reforms. For instance, Forrester and Adams (1997, p. 473) found that “the chance for successful budget reform increases if executive budget participants and program managers support the goals and objectives of the budget initiative and the legislature participates in the planning process.” They also found that there also must be buy‐in from budget office staff and agency leadership. In many efforts to reform the budget, agencies go through the motions rather than attempting to sincerely implement the reform.…”
Section: Enabling Factors For Grb Successmentioning
confidence: 99%
“…“Aligning budgetary reform with organizational culture dramatically raises the likelihood of the personal and organizational ownership necessary for successful reform. Ownership is key because it provides the foundation for successful reform” (Forrester and Adams 1997, p. 475).…”
Section: Enabling Factors For Grb Successmentioning
confidence: 99%
“…But the call for a more rational set of decision rules for making allocation decisions persisted, and the gap between normative and descriptive theory varied between wide and wider. Forrester and Adams (1997) offered a more expansive way to think about budget theory. Normative theory is a theory of budgeting, while descriptive theory is a theory about budgeting.…”
Section: Normative and Descriptive Budget Theorymentioning
confidence: 99%
“…In the complexity of organizational change phenomena (Johnson et al, 2000;Cyert, 1990) and tendency towards change resistance among the followers (Forrester & Adams, 1997;Dawson, 1994;Child & Smith, 1987) the characteristic of transformational leadership is necessary. Studies on the efforts to change an organizational management accounting practice have documented the environmental complexity and followers' resistance (Coram & Burnes, 2001;Abdul Rahman, 1993).…”
Section: Leadership Characteristicmentioning
confidence: 99%